The Influence of Epistemic Beliefs on Master’s Students’ Critical Thinking in Academic Reading - Mia Dreina Antira Pujiningtyas; Paulus Kuswandono (Universitas Sarjanawiyata Tamansiswa, 2022)
The understanding of how an individual perceives knowledge and knowing is called epistemic beliefs. Moreover, Epistemic beliefs are also closely related to critical thinking. This study investigates the effects of epistemic beliefs on critical thinking, specifically in reading. There are two research questions formulated in this study which are: (1) What are the master’s students' epistemic beliefs level in reading? and (2) How do epistemic beliefs affect their critical thinking in reading? The participants of the study consisted of 12 graduate students from a private university in Yogyakarta. Descriptive quantitative and descriptive analysis were employed. The data were collected using a close-ended questionnaire and open-ended questions. The Justification for Knowing Questionnaire (JFK-Q) from Ferguson et al. (2013) was adapted for this study. Open-ended questions functioned as the follow-up of the questionnaire. The result showed that the graduate students’ epistemic beliefs were classified as sophisticated. The possessed beliefs helped to activate, hone, and improve the student’s critical thinking in reading.